2003
DOI: 10.1007/s10350-004-6553-x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Removal of Large Colorectal Polyps

Abstract: Endoscopic polypectomy is a safe and effective method of treating large colorectal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
2
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(83 citation statements)
references
References 22 publications
8
65
2
8
Order By: Relevance
“…In this study, we described a series of 1354 endoscopic resections of colon rectal polyps performed in our endoscopic units between January, 1996 and May, 2006. The gender and age distribution of patients is similar to that described above in other studies regarding the treatment of colorectal polyps [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . From the literature, it emerges that over 80% of polyps resected during colonoscopy are small polyps less than 10 mm in diameter [24] while in our study 67% were 10 mm in diameter.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…In this study, we described a series of 1354 endoscopic resections of colon rectal polyps performed in our endoscopic units between January, 1996 and May, 2006. The gender and age distribution of patients is similar to that described above in other studies regarding the treatment of colorectal polyps [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . From the literature, it emerges that over 80% of polyps resected during colonoscopy are small polyps less than 10 mm in diameter [24] while in our study 67% were 10 mm in diameter.…”
Section: Discussionsupporting
confidence: 59%
“…The incidence of bleeding during and after the polypectomies has been reported to range from 0.3% to 6.1%, with higher rates in large polyps up to 22.1% (Table 6) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . In our series, the Pearson χ 2 test applied in the subgroups found a correlation between the bleeding and liver diseases (P = 0.003), which usually impairs the coagulation function of the patients and location of polyps in transverse colon (P < 0.0001), in group 2 with histology and in particular with the hyperplastic polyps (P = 0.023) and the malignancy (P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bleeding is considered the most common complication, occurring in 0.4% to 16% of cases (8,15,32,48) . Ferrara et al (10) concluded that bleeding was significantly related to malignancy, as observed in one of our cases.…”
Section: Discussionmentioning
confidence: 99%